Frankenstein - Shelley, Mary; Stocks, Mike; Jones, Barry (London, Usborne pPublishing Ltd, 2006)
As lightning flashes across the night sky, Victor Frankenstein succeeds in the ultimate scientific experiment - the creation of life. But lonely and rejected, the being he creates soon turns on Victor and his family, with terrifying and tragic results. Rivetingly retold for a new generation of readers, Mary Shelley's classic horror story remains as powerful and gripping as the day it was first written. Includes informative notes on both the author and the original text
Keywords: English fiction